Recurrence rate in early-stage epithelial ovarian cancer: Is there a role for upfront maintenance with PARP inhibitors in stages I and II? - Monica D. Levine; David M. O'Malley; Paulina J. Haight; Leigha Senter; Vincent Wagner; Kristin L. Bixel; David E. Cohn; Larry J. Copeland; Casey M. Cosgrove; Eric M. McLaughlin; Floor J. Backes (Elsevier, 2023)
Objective: To determine the recurrence rate and survival among early-stage epithelial ovarian cancer cases considering homologous recombination deficiency (HRD) status. Methods: Single institution retrospective study of stage I/II EOC patients from 2017 to 2020. HRD was defined as evidence of germline or somatic BRCA mutation, or loss of heterozygosity (LOH)/genomic instability (GIS) as determined by companion diagnostic tests. Kaplan-Meier analyses were performed. Results: 89 stage I/II cases were included. 4/89 (4.5%) had a germline BRCA1/2 mutation, 8 (9%) were germline negative but had a somatic BRCA mutation, and 8 (9%) were BRCA wild-type but had evidence of LOH/GIS on somatic testing; these 20/89 (22%) cases comprised the HRD group. The remaining tumors were confirmed homologous recombination proficient (HRP, 35/89, 39%) or homologous recombination unknown (HRU, 34/89, 38%). The overall recurrence rate was 33/89 (37%). There were more recurrences among HRD cases (14/20, 70%) compared to HRP/HRU cases (19/69, 27.5%, p = 0.0012). Median Recurrence-Free Survival (RFS) was 35 months for HRD cases and 225 months for HRP/HRU cases (p = 0.001). At 2 years, there were 60% HRD cases and 88% HRP/HRU cases recurrence-free. At 5 years there were 29% HRD and 69% HRP/HRU cases recurrence-free (p = 0.001). Conclusions: Despite a high rate of complete surgical staging and six cycles of adjuvant chemotherapy, recurrence rate was high in this early-stage cohort. Higher recurrence rates were seen in the HRD group, however these data are likely biased by the clinical practice of tumor testing primarily at the time of recurrence rather than the upfront setting. RFS was significantly lower for HRD cases.